The fractionary Schrödinger equation, Green functions and ultradistributions - de Paoli, Ángel Luis (2013)
In this work, we generalize previous results about the Fractionary Schrödinger Equation within the formalism of the theory of Tempered Ultradistributions. Several examples of the use of this theory are given. In particular we evaluate the Green function for a free particle in the general case, for an arbitrary order of the derivative index.